2014
DOI: 10.1159/000355143
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Dementia: Characteristics and Clinical Features in Consecutive Series of Patients

Abstract: Background/Aim: The prestroke level of cognitive function should be taken into account in order to predict the impact of stroke on the subsequent risk of dementia. The aim of the present study was to investigate the presence and correlates of prestroke dementia (PSD) as well as to identify its clinical features. Methods: Premorbid clinical and cognitive features of 158 consecutively recruited patients with a diagnosis of acute cerebrovascular pathology were assessed by interviewing the caregivers using multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Стоит отметить, что наличие предшествующего когнитивного снижения становится предиктором тяжести постинсультного когнитивного дефекта [23], а нейропсихологический дефицит, выявленный по результатам IQCODE, может быть неоднороден по своей структуре. Так, предшествующие когнитивные нарушения могут иметь не только сосудистую, но и нейродегенеративную этиологию [24]. Поэтому постинсультные когнитивные нарушения часто бывают представлены смешанным когнитивным дефицитом (сосудистое поражение головного мозга в сочетании с болезнью Альцгеймера).…”
unclassified
“…Стоит отметить, что наличие предшествующего когнитивного снижения становится предиктором тяжести постинсультного когнитивного дефекта [23], а нейропсихологический дефицит, выявленный по результатам IQCODE, может быть неоднороден по своей структуре. Так, предшествующие когнитивные нарушения могут иметь не только сосудистую, но и нейродегенеративную этиологию [24]. Поэтому постинсультные когнитивные нарушения часто бывают представлены смешанным когнитивным дефицитом (сосудистое поражение головного мозга в сочетании с болезнью Альцгеймера).…”
unclassified
“…Previous studies have indicated lower prevalence estimates of pre-SCI, but some of these have used 4.0 as the IQCODE cutoff for the definition of pre-SCI, 21 23 thus restricting the investigation to the most severe forms of pre-SCI. When comparing our study with others that used the same IQCODE cutoff, 2 , 3 our study still has a higher prevalence of pre-SCI, which could be explained by the higher age of our cohort, but also by some differences in the inclusion criteria. Mok et al 2 have studied a small number of patients with an ischemic stroke associated with small vessel disease, excluding patients with other stroke etiologies.…”
Section: Discussionmentioning
confidence: 61%
“… 1 When including the milder forms of cognitive impairment, prevalence estimates are higher, reaching 24% in some studies. 2 , 3 Part of the variability in the epidemiology of pre-SCI depends on the lack of a standardized diagnosis. Some studies have relied on the medical history or clinical interview for the definition of pre-SCI, 4 , 5 while others have used informant-based questionnaires, 2 , 3 which allow a more reproducible assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suction drains are typically used to improve tissue adhesion, minimize seroma formation and to monitor for fistula. Patients are typically placed on antibiotics and a proton pump inhibitor .Patients are initially fed via a nasogastric tube or previously established G‐Tube. The time to oral feeding is surgeon dependent and may be contingent upon a barium swallow.…”
Section: Types Of Operationsmentioning
confidence: 99%